MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA DINI MELALUI PERMAINAN BOWLING KALENG - Rosa Imani Khan dan Ninik Yuliani (IAIN Kediri, 2016)
This study aimed to improve early childhood numeracy skills through the game of â€œBowling Kalengâ€. Numeracy is the ability of every child in terms of mathematics such as sort of numbers or counting and know the number. Development of childrenâ€™s numeracy skills can do through the game. This would be more effective because the childrenâ€™s world is playing world, one of which is the game of â€œBowling Kalengâ€. Research was conducted on 30 children in Group B TK Dharma Wanita Gogorante Kediri. Those aged 5 to 6 years old, consists of 16 boys and 14 girls. The method used in this study is classroom action research using two cycles. Each cycle consists of four phases: planning, action, observation and reflection. The study was conducted at the beginning of January 2016. The results of this study indicate that learning through the â€œBowling Kalengâ€ game can improve childrenâ€™s numeracy skills. The average of childâ€™s ability to counting, add up dan reduce numbers increased to the last cycle. Through this game, children learn to count concrete objects they like in a cheerful and pleasant atmosphere.Keywords; Numeracy skills, early childhood, Bowling Kaleng game